2017
DOI: 10.3390/s17081841
|View full text |Cite
|
Sign up to set email alerts
|

Applying Sensor-Based Technology to Improve Construction Safety Management

Abstract: Construction sites are dynamic and complicated systems. The movement and interaction of people, goods and energy make construction safety management extremely difficult. Due to the ever-increasing amount of information, traditional construction safety management has operated under difficult circumstances. As an effective way to collect, identify and process information, sensor-based technology is deemed to provide new generation of methods for advancing construction safety management. It makes the real-time co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 89 publications
2
73
0
Order By: Relevance
“…The current studies and applications only utilize a single system or technology. The authors of [40] discuss that systems that are based on single systems are not practical enough, but conversely, the complex sensor systems can yield satisfying results. Therefore, to advance the effectiveness of emerging technologies to achieve current challenges faced in the construction industry, there is a need for a comprehensive and interoperable IoT-based system that can be adaptable to the variety of sensors, technologies, and applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current studies and applications only utilize a single system or technology. The authors of [40] discuss that systems that are based on single systems are not practical enough, but conversely, the complex sensor systems can yield satisfying results. Therefore, to advance the effectiveness of emerging technologies to achieve current challenges faced in the construction industry, there is a need for a comprehensive and interoperable IoT-based system that can be adaptable to the variety of sensors, technologies, and applications.…”
Section: Discussionmentioning
confidence: 99%
“…Sensors have helped in the development and advancement of safety studies. The authors of [40] comprehensively review the application of sensor technology in construction safety studies and emphasize the role of smartphones as a comprehensive sensor set which are always on a person. Smart phones' numerous advantages and ease of accessibility turns them into an optimal choice.…”
Section: Iot For Construction Safetymentioning
confidence: 99%
“…RFID's have the capability to track positions of RFID tags with varying accuracy, depending on the location and the arrangement of the readers in relation to the tags. Research done on using RFID's for locating objects on construction sites showed 3.7-meter positional error [4,5,6]. Better results were obtained in other studies which demonstrated a 1.3-meter average positional error [7].…”
Section: Research In Rfid Applications In Construction For Productivitymentioning
confidence: 97%
“…The main role of sensor is to acquire information. Sensor is used to help dealing with several issues on safety and security, energy monitoring and control, environmental protection and health (Ho et al, 2005, Patel et al, 2012, Zhang et al, 2017.…”
Section: Introductionmentioning
confidence: 99%